Правовий аналіз причин трудових розбіжностей - Сокол, М.; Sokol, M. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті розкрито основні причини розбіжностей між сторонами соціально-трудових відносин. Проана- лізовано норми законодавчих актів та дані статистики, на основі яких визначено чотири основних групи причин, що спонукають до виникнення колективних трудових спорів, і наведено можливі шляхи запобігання виникненню конфліктних ситуацій.In the article the main causes of disagreements between the subjects of social-labor relations are defined. Norms of the legislation and the statistics, on which four main groups of reasons to encourage the emergence of collective labor disputes were defined, are analyzed, namely: the reasons of a subjective nature, objective nature, organizational and legal nature, organizational and economic nature. It is proposed to establish a particular measure of responsibility for the employer for late responding to the differences that have emerged, and for no warning the relevant authorities about their appearance. This would reduce the number of labor disputes, their faster resolving with minimal time and material resources.
The Legal Analysis of the Causes of Labor Disputes.
Keywords: колективний трудовий спір; причини спорів; шляхи подолання спорів; collective labour disputes; causes of disputes; ways to overcome disputes